Pengaruh Faktor Lingkungan Keluarga terhadap Minat Berwirausaha - Aulia Monica; Zuhrinal M. Nawawi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Interest in entrepreneurship is the desire, interest, and willingness of individuals to work hard in fulfilling their life needs without fear of the risks that will occur. The analysis used in this observation is descriptive qualitative, with a literature review methodology that uses several sources such as journals as the main reference for conducting research. The results obtained. Interest in entrepreneurship will arise if someone has gained a lot of knowledge horizons about entrepreneurship either from the experience of others or from the experience of others. entrepreneurship book. Someone who is already interested and interested in becoming an entrepreneur will be more familiar with activities related to entrepreneurship. knowing about entrepreneurial activities. It can be concluded that the environment is very influential and supportive for entrepreneurship, then the interest in entrepreneurship will be even greater. Family environment has a positive effect on Entrepreneurial Interest. Keywords: environment, family, entrepreneur